Blastocystis: Pathogen or Passenger? An Evaluation of 101 Years of Research - Mehlhorn, Heinz; Tan, Kevin S. W.; Yoshikawa, Hisao; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
The stages of Blastocystis have been known for 101 years. However, many facts are still disputed, e.g. even the question whether it is a true pathogen or a commensal present in sometimes life-threatening diarrheas. The present book evaluates in chapters contributed by renowned researchers the latest findings on: •Landmarks in the discovery of Blastocystis •Epidemiology, transmission and zoonotic potential •Morphology of human and animal Blastocystis isolates •Clinical aspects of Blastocystis infections •Behavioral decision analysis: what makes us sick? •Blastocystis-host interactions •Molecular approaches on the systematical position •Genetic polymorphism •Blastocystis from a statistical point of view •Diarrheas due to different agents of disease •Zoonotic diseases in comparison As such, this book provides a broad range of information for people working in this field, for physicians and veterinarians who are confronted with clinical cases, teachers, students and technical staff members in the fields of microbiology, parasitology and diagnostic methods.
Landmarks in the discovery of Blastocystis stages -- Morphology of human and animal Blastocystis isolates with special references to reproductive modes -- Epidemiology, transmission and zoonotic potential of Blastocystis stages in humans and animals -- Blastocystis – Host interactions: insights from in-vitro model systems -- Clinical aspects of Blastocystis infections: advancements admidst controversies -- Molecular approaches on systematic position, genetic polymorphism and classification of Blastocystis isolates from humans and animals -- What do we know about Blastocystis analyzing research studies with statistical methods -- Behavioral decision analysis: how do we decide what makes us sick? -- Diarrheas in humans due to agents of diseases -- What are zoonotic diseases? -- Conclusions.
Keywords: Parasitology; Medical microbiology; Health promotion; Parasitology; Medical Microbiology; Health Promotion and Disease Prevention